1995
DOI: 10.1105/tpc.7.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-dependent transport of the NADPH:protochlorophyllide oxidoreductase into isolated plastids.

Abstract: The key regulatory enzyme of chlorophyll biosynthesis in higher plants, the light-dependent NADPH:protochlorophyllide oxidoreductase (POR), is a nuclear-encoded plastid protein. Its post-translational transport into plastids is determined by its substrate. The precursor of POR (pPOR) is taken up and processed to mature size by plastids only in the presence of protochlorophyllide (Pchlide). In etioplasts, the endogenous level of Pchlide saturates the demands for pPOR translocation. During the light-induced tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 60 publications
2
97
0
Order By: Relevance
“…This idea is supported by the fact that POR-A is imported into plastids in a protochlorophyllide dependent way (Reinbothe et al 1995(Reinbothe et al , 1996.…”
Section: Light-dependent Protochlorophyllide Oxidoreductasesupporting
confidence: 58%
“…This idea is supported by the fact that POR-A is imported into plastids in a protochlorophyllide dependent way (Reinbothe et al 1995(Reinbothe et al , 1996.…”
Section: Light-dependent Protochlorophyllide Oxidoreductasesupporting
confidence: 58%
“…However, if the effect is physiological, Walker and Willows (1997) have suggested that the results can be reconciled if the buildup of intermediates inhibits the import of one or more of the Mg-chelatase subunits into the chloroplasts. Such a mechanism has been proposed for the regulation of protochlorophyllide reductase import (Reinbothe et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In angiosperms such as barley, Arabidopsis (1, 2), tobacco (3) and Amaranthus tricolor (4), and gymnosperms such as pine species (5-7), several por gene families were identified that encode highly conserved POR polypeptides. PORA represents the negatively light-regulated POR enzyme whose level drops as a result of the concerted effect of light at the levels of transcription, mRNA stability, plastid import, and protein degradation after light-induced catalysis (8)(9)(10)(11). PORB, the second POR protein identified in barley and Arabidopsis (1,12), is constitutively expressed in darkgrown, illuminated, and light-adapted plants (see ref.…”
mentioning
confidence: 99%